Vacuna antirrábica preparada con una cepa viral aislada de murciélago vampiro (Desmodusrotundus) - Hernández B., Eliseo (Avances en Ciencias Veterinarias, 1989)
A plaque–purified experimental rabies vaccine was developed from an isolate (strain V–319) made from a naturally infected vampire bat (Desmodus rotundus). Two different vaccines were prepared: one was live virus and the second was an inactivated rabies virus preparation. The live virus vaccine and betapropiolactotie–inactivated vaccine, gave complete protection to challenge inoculation after 1 year. The strain (V–319) could be distinguished from other vaccinal strains by the nature of the plaque morphology. It is conclude that a safe living rabies vaccine of high potency and efficacy in cattle has been developed, and successfully, tested in Mexico under stringent field conditions. Key words: rabies, vaccine, virus, cattle.